Do Dairy Minerals Have a Positive Effect on Bone Health?. Issue 4 (6th June 2018) - Burrow, Keegan; Young, Wayne; McConnell, Michelle; Carne, Alan; Bekhit, Alaa El‐Din
Abstract: This review aims to examine the relationship between the consumption of dairy products, mineral absorption, and bone health, and critically evaluates the methods that have been used to investigate this relationship. As people live longer and have lives that are more active in modern societies, bone health is of concern due to the possibility for the increasing incidence of bone disorders, such as osteoporosis. It has been suggested that dairy products can play a key role in bone health due to their high levels of minerals. Whether the positive effect of dairy consumption on bone health is due solely to the concentration of minerals, the action of vitamins, proteins, and lipids present in dairy products, and complex interactions between different milk components remains to be determined. Assessment of how dairy products affect bone health is complex, with apparent contradictory conclusions being reported in the literature. To gain a better understanding of the effects that dairy products have on bone health, this review presents an evaluation of a combination of data obtained using a variety of methods. From those data, we surmise that the preferable approach to investigate the effects of milk on bone health is to obtain data from human, animal, and cell line testing. A combined approach will enable various aspects to be identified, including mechanisms and the assessment of holistic effects, which will enable the effects in the human situation to be ascertained.